Attachment play narratives: a window to the childs mind (Revista de Psicología, 2019)
The present work discusses the rationale of changes in attachment measurement from infancy to childhood. Attachment play narratives used to classify attachment representations are described. Their use in research and clinical work is also discussed. The value of attachment play narratives in clinical work is posed as a tool both for clinical assessment to identify relational patterns, and for therapeutic practice to enhance parental reflexive function. To portray the way in which play narratives can evoke attachment representations, four vignettes of The Manchester Child Attachment Story Task (J. Green, C. Stanley, V. Smith & R. Goldwyn, 2000) are transcribed and analyzed. These vignettes were completed within a clinical research work (I. Di Bartolo, 2009).
Keywords: attachment; play narratives; middle childhood; attachment story stems; clinical practice